Integration of E-learning System through Mobile Technology - Caraig, Glenn A.; Iyo, Jr., Gregorio E.; Kelechi, Ejeka Smart; Caraig, Marianne E. (International Journal of Computing Sciences Research, 2020)
Purpose   – This paper aims to identify the most commonly used E-learning resources in the classroom among Elementary Education students in one of the Local University and Colleges (LUCs) in Batangas, Philippines and evaluates the use of mobile technology and E-Learning System in terms of functionality, usability, efficiency, and reliability based on ISO 9126 evaluation standard. Method – The researchers utilized a self-made questionnaire to gather necessary data to evaluate the E-Learning system based on the ISO 9126 software quality metrics. The questionnaires consisted of three parts: profile of the participants; E-Learning System and E-Learning resources; evaluation of E-Learning System in terms of functionality, reliability, usability, and efficiency. The participants were ninety-three students: nondisabled and students with hearing and speaking problems. Results – The most commonly used E-Learning resources in the classroom by the students were laptop computers, smartphones, mobile applications, internet, and video tutorials. It was found out that the E-learning system is highly functional, highly usable, highly efficient, and reliable through the use of mobile technology. This study also shows that there is no significant difference between the assessments of nondisabled students and students with disabilities using the E-Learning System. The participants stated that E-learning system increases the quality of learning because it integrates all forms of media. Conclusion – Students and teachers were willing to embrace the E-Learning system, there is still a need of access other E-Learning resources, and ICT platforms.  As depicted in the result of the study, since the computed values of all variables did not exceed the tabular value, the null hypotheses are hereby accepted. This implies that there is no significant difference between the assessments of nondisabled students and students with disabilities with regards to the E-Learning System. Recommendations – Internet connectivity should be a priority to be established to benefit all the delivery models such as face-to-face, self-paced, and individualized learning along with virtual interactions. Integrating mobile learning may help overcome the concerns with connectivity and convenience to a great extent. Leveraging on the utilization of mobile phones, there should be regular capacity-building activities and skills enhancements on E-Learning System and other related software and tools among the professors, and students. E-learning designers may consider the existence of the users with hearing and speaking disabilities to develop an e-learning environment that may be effective to all users generally. Practical Implications – Academic institutions would be able to adopt the same approach of using E-learning system though mobile technology to handle students with speaking and hearing problems in delivering teaching and learning.